Implementation of the Distribution of the Jatim Puspa Program Through Special Financial Assistance for Community Empowerment in Kediri District - Utomo Nova Arianto, Nova (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The Jatim Puspa Program, a poverty alleviation initiative in East Java, focuses on improving the welfare of Beneficiary Families (KPM). Designed to maximize effectiveness in rural areas, this program empowers KPM who have completed the Jatim Puspa Program. By providing direct assistance and guidance, this program aims to empower the community, especially KPM, in Kediri Regency. Descriptive qualitative research evaluating the implementation of the Jatim Puspa Program uses the Van Meter and Van Horn model to analyze six variables: policy standards, resources, communication between institutions, characteristics of implementers, social, economic and political conditions, and disposition of implementers. Data analysis includes collection, reduction, presentation, conclusions and verification. The research results reveal that there is still a gap in public understanding of program mechanisms, low KPM commitment, and dependence on government assistance. Therefore, it is necessary to increase community assistance for the smooth running of the program and achievement of poverty alleviation targets in Kediri Regency. Recommended follow-up actions include increasing motivation and guidance for KPM, adding program assistants, and increasing access to health and education services.